(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Military personnel with developed psychophysical qualities have a higher likelihood of success in their profession. The development of psychophysical preparedness can help maintain efficiency and health in extreme conditions. Today, there is a need to improve the psychophysical training of security and defense sector personnel in Ukraine. Engaging in sports can be one of the possible ways to enhance the psychophysical preparedness of the personnel in the security and defense sector of Ukraine. However, differences in psychophysical indicators between cadet-athletes and cadets without sports experience in the conditions of full-scale war have not been determined. This complicates the process of forming recommendations for developing physical training programs for cadets. Research methods used include theoretical analysis and summarization of scientific-methodical literature and internet data, sociological surveys (questionnaires), and methods of mathematical statistics. Results have confirmed that sports activities have a positive impact on the psycho-emotional state of cadets: they shape a higher level of life satisfaction, personal stress resistance (without affecting situational anxiety); they increase the ability to control anger without affecting the ability to control emotions of depression and anxiety. Similar tendencies were observed for other psychophysical state indicators, which, however, did not statistically confirm, possibly explained by their heterogeneity. It can be recommended to engage in sports for the correction of the psychophysical state of cadets in higher education institutions during wartime conflicts.